Animal Models of Complex Regional Pain Syndrome Type I - Liu Y (Dove Medical Press, 2021)
Yu Liu,1 Ying Liang,1 Min Gao,1 Yingchun Li,1 Tingting Zhao,2 Yani Zhao1 1Third Hospital of Shanxi Medical University, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Taiyuan, Shanxi, 030032, People’s Republic of China; 2Shaanxi University of Traditional Chinese Medicine, Xi’an, Shaanxi, 712046, People’s Republic of ChinaCorrespondence: Ying LiangThird Hospital of Shanxi Medical University, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Taiyuan, No. 99, Longcheng Street, Xiaodian District, Taiyuan, Shanxi, 030032, People’s Republic of ChinaTel +86-13934225687Email sx.liangying@126.comAbstract: Complex regional pain syndrome (CRPS) is a chronic pain disorder characterized by spontaneous or evoked regionally-confined pain which is out of proportion to the initial trauma event. The disease can seriously affect the quality of the patients’ life, increase the psychological burden, and cause various degrees of disability. Despite the awareness of CRPS among medical practitioners for over a century, its pathogenesis remains unclear, and the available treatment is still unsatisfactory. Effective animal models are the foundation of disease research, which is helpful in understanding the pathogenesis and an in-depth exploration of the appropriate therapeutic approaches. Currently, researchers have established a series of animal models of the disease. There are four main CRPSI animal models: chronic post-ischemic pain (CPIP) model, tibial fracture/cast immobilization model, passive transfer-trauma model, and the needlestick-nerve-injury (NNI) model. The modeling methods of these models are constantly improving over time. In preclinical studies, the interpretation of experimental results and the horizontal comparison between similar studies may be affected by the nature of the experimental animal breeds, sex, diet, and psychology. There is need to facilitate the choice of appropriate animal models and avoid the interference of the factors influencing animal models on the interpretation of research results. The review will provide a basic overview of the influencing factors, modeling methods, and the characteristics of CRPSI animal models.Keywords: CRPS, reflex sympathetic dystrophy, animal model, mouse, rat, sex, diet, psychology